The Degree of Assertiveness in Speeches Delivered by Debaters on NSDC 2020 Final Round - Azhar Maulana Maghribi Sidiq; Sri Wuli Fitriati; Widhiyanto Widhiyanto (Universitas Negeri Semarang, 2023)
Considering the crucial roles of interpersonal meaning in argumentative speech, the study evaluated the use of interpersonal meaning using Halliday’s theory (2014) in debate speeches. It aimed to find out the use of mood and modality in the speech of debaters and how mood and modality realize assertiveness. This research used a qualitative research design with the data from spoken language, especially the final round of the National School Debating Championship 2020. The result of the study on 6 high school debaters showed that there are 1061 mood systems found; they are classified as declarative, interrogative, and imperative mood systems. The most occurred mood in the speech was the declarative mood, which is 999 clauses and categorized as a statement that contains information for the debater to present their idea. The presented ideas were used in an attempt to justify the team’s stances. The modality system found that the most common type of modality in speech was the inclination modality, which is 40 clauses. It indicates that the debater wants to show their determination on how the debater deals with the motion. By analyzing the speech using interpersonal meaning, the highest number of declarative mood and inclination modalities indicates the assertiveness in every debater’s speech.